Language Preference and Diglosic Practice Among Islamic Boarding School Students: A Case Study in Sociolinguistics - Masnawati; Andi Rachmawati Syarif; Syarif Amin; Ibrahim Manda (Universitas Islam Negeri Palopo, 2026)
This study investigates language preference and diglosic practices among students at an Islamic boarding school in Indonesia, where Arabic, English, and Indonesian coexist in daily communication. Language choice is shaped by sociocultural domains and institutional norms (Fishman, 1972; Holmes, 2013). Although Arabic and English are officially promoted, their use reflects unequal functional distribution consistent with classical diglossia (Ferguson, 1959). Using a qualitative case study design (Creswell & Poth, 2018), data were collected through non-participant observations, semi-structured interviews, and document analysis. Data were analyzed using Miles, Huberman, and Saldaña’s (2014) interactive model. Findings indicate the dominance of Arabic in religious activities and peer interaction, while English is largely limited to classroom instruction. Arabic functions as a high-status variety linked to religious authority and institutional ideology (Ferguson, 1959), whereas English occupies a restricted pedagogical role shaped by language policy and symbolic capital (Bourdieu, 1991; Spolsky, 2004). The study highlights how institutional ideology sustains diglosic hierarchies in Islamic boarding school contexts.